2020
DOI: 10.21831/jpv.v10i1.30378
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of block-system learning on the expertise competence of automotive lightweight vehicle engineering in vocational high school

Abstract: The objective of this study was to understand the following: (1) the effectiveness of block system learning to student learning outcomes. (2) the diffrences in student learning outcomes between those who use block and non-blok learning system in public vocational high schools in Batang District. This study includes a type of descriptive quantitative research with a survey approach. Data were collected through observation, interview, and documentation. The population is the whole school vocational high schools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The results of the certification competency test from students will be an indicator of achievement of graduate competency standards, while for stakeholders it will be used as information on the competencies of prospective workers. The implementation of the competency certification test still needs to be improved, namely on the indicators of technological progress that are used during the implementation of the competency test so that it can be adjusted to the existing technology in the industry today (Burhan & Arifin, 2020;Setyaningrum & Purwati, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the certification competency test from students will be an indicator of achievement of graduate competency standards, while for stakeholders it will be used as information on the competencies of prospective workers. The implementation of the competency certification test still needs to be improved, namely on the indicators of technological progress that are used during the implementation of the competency test so that it can be adjusted to the existing technology in the industry today (Burhan & Arifin, 2020;Setyaningrum & Purwati, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Class management is carried out by considering the competencies that will be achieved in learning (Cristea, 2015). some schools implemented a block system in practical learning as well, as in a preliminary study, several schools implemented a block system in practical learning in the pandemic era (Burhan & Arifin, 2020). The results of the research found in Table 4 state that in the implementation of offline theory and practice learning the teacher chose to use a half-class system with student restrictions and combined it with online classes with the rest of the students who did not practice offline.…”
Section: Class Managementmentioning
confidence: 99%
“…Of these, graduates from Vocational High Schools (SMK) contributed the highest number of unemployed, namely 9.42%. This statement is inversely proportional to the purpose of SMK which is held to create a ready-to-use workforce according to their field of expertise (Burhan & Arifin, 2020;Lawitta et al, 2017). The high unemployment rate for SMK graduates is the impact of the low work readiness of SMK students (Afriadi et al, 2018;Sudarsono, 2022;Syofyan, 2022).…”
Section: Introductionmentioning
confidence: 99%